Ethical Guidelines for Artificial Intelligence in Healthcare from the Sustainable Development Perspective - Leimanis, Anrī; Palkova, Karina (European Journal of Sustainable Development, 2021)
Use of Artificial Intelligence (AI) in variety of areas has encouraged an extensive global discourse on the underlying ethical principles and values. With the rapid AI development process and its near instant global coverage, the issues of applicable ethical principles and guidelines have become vital. AI promises to deliver a lot of advantages to economic, social and educational fields. Since AI is also increasingly applied in healthcare and medical education areas, ethical application issues are growing ever more important. Ethical and social issues raised by AI in healthcare overlap with those raised by personal data use, function automation, reliance on assistive medical technologies and the so-called ‘telehealth’. Without well-grounded ethical guidelines or even regulatory framework in respect of the AI in healthcare several legal and ethical problems at the implementational level can arise. In order to facilitate further discussion about the ethical principles and responsibilities of educational system in healthcare using AI and to potentially arrive at a consensus concerning safe and desirable uses of AI in healthcare education, this paper performs an evaluation of the self-imposed AI ethical guidelines identifying the common principles and approaches as well as drawbacks limiting the practical and legal application of internal policies. The main aim of the research is to encourage integration of theoretical studies and policy studies on sustainability issues in correlation between healthcare and technologies, the AI ethical perspective.